우즈베키스탄 농촌주택 에너지효율화를 위한 대안 분석 및 표준모델 제안 - 조경주(Cho, Kyung-Joo); 조동우(Cho, Dong-Woo); 정영선(Jeong,Young-Sun) (KIEAE Journal, 2018)
Purpose: The energy consumption in Uzbekistan buildings accounts for more than half of the total energy consumption in Uzbekistan. In particular, Uzbekistan is estimated to produce 100 million tons of carbon dioxide per year only through the use of building energy. In particular, residential buildings have caused the largest energy consumption in Uzbekistan. For this reason, this study analyzed the standard rural housing plans of Uzbekistan and suggested energy saving alternatives by improving the insulation performance. Method: This research was conducted in four stages. For the first step, preliminary investigations were carried out such as climate analysis of Uzbekistan and prior studies on Uzbekistan buildings’ energy consumption. For the second step, the Uzbekistan building regulations were analyzed in order to improve the standard rural housing in Uzbekistan and confirm the direction of the alternatives. For the third step, the analysis of the rural housing plans were conducted to optimize the design of the AOP system to be installed in Tashkent. Finally, simulation results of energy efficient alternatives were compared with the result of existing standard rural housing and the model house constructed in Tashkent. Result: Energy efficient alternatives were calculated to consume 64%~76% less heating energy than the existing standard rural housing. KCI Citation Count: 0